General prevention of corruption and bribery in the Republic of Belarus - Khlus , A.M. (Bulletin of the Karaganda University “Law Series”, 2021)
The article examines prevention as the most important direction in combating corruption and bribery. Based on the analysis of the current anti-corruption legislation, the author concluded that there is insufficient attention on the part of state bodies to prevention as one of the areas of anti-corruption. Attention is drawn to the “pinpoint” nature of the measures taken in connection with the fight against corruption, which, in their essence, perform the role of preventing the commission of new crimes of corruption. In the course of the study the author came to the conclusion that it is necessary to consider the problems of combating corruption and bribery in the aspect of their prevention. For this purpose it is proposed to create certain conditions, and take effective measures aimed at restructuring the psychology of consciousness of a modern person. According to the author, the education of the young generation, designed to form a system of certain rules of behavior in various spheres of life, should be the fundamental part of prevention. In this regard, attention is focused on the need for the formation of managerial potential in the system of conditions of the strictest education. Ideally, the system of educating a potential manager should be based on an extremely negative perception of everything related to corruption and, no less important, eradicate various examples of corrupt relations. In order to prevent corruption and bribery it is proposed to limit the duration of civil service in sectors and spheres of activity characterized by a high degree of probability of the formation of corruption relations, by the termsdetermined by legislation. It is also necessary to expand the possibilities of applying the personnel rotation mechanism, and the extension of the terms of activity of individual officials should be carried out after a preliminary check of their previous activities.